The environmental choice of dance image in humanities documentary - Yaakup, Hani Salwah; Yu, Kun; Syed Zainudin, Sharifah Sofiah; Mohammad Razi, Siti Aishah (Human Resource Management Academic Research Society, 2022)
Adding dance images to humanistic documentaries can be used to modify the content of the film. In particular, the environment in which the dance is displayed can affect the effect of the dance image expression, thereby advancing the narrative of the storyline. Based on the existing literature related to dance images, only the importance of location selection is discussed, and literature related to environmental selection is lacking. At the same time, there is no discussion on the classification of environmental selection in the related literature of dance image. The research method of this paper is the text analysis of case studies, which are classified and summarized by four cases to explore the emotional expression of dance in different environments. The purpose of the research is to determine the importance of the selection of the appropriate environment for the expression of the meaning of the image, which can be divided into several categories. The right environment in the dance itself helps to grasp the key points of dance body language. And in the dance image, the importance of the correct choice of environment and the cooperation of dance to the overall narrative of the documentary. Through the analysis of this research, it can be found that the basic situation of the environment selection in the existing dance images, at the same time, the related literature is summarized to open up the way for the literature research of dance image environment selection, which is convenient for further research on related topics in the future.